DIASPORA ENTREPRENEURSHIP IN JAPAN: DEVELOPING HALAL BUSINESS IN A NON-MUSLIM MAJORITY COUNTRY - Shobichatul Aminah; Nova Rini; Brisbania Ayu Saraswati Bhakti; Eldwita Nofrelia; Mutiara Rachmadini Effendi; Satomi Ohgata (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2026)
The issue of ethnic inequality among immigrant communities in host countries often poses a challenge for diaspora entrepreneurs seeking to develop their businesses. The Indonesian Muslim diaspora in Japan also faces challenges in developing their halal businesses, as they must compete with local entrepreneurs, who have greater access to expansion opportunities. This study examines the strategies implemented by Sariraya enterprise , founded by the Indonesian Muslim diaspora, for developing and maintaining halal businesses in Japan as a country with a non-Muslim majority . Using a qualitative research approach including observation and in-depth interviews, this study explores how adaptation and social networks support the development and sustainability of Sariraya businesses. In-depth interviews were conducted with 20 respondents including the founder, staff of the Sariraya business network (Indonesian, Nepalese, and Vietnamese), and customers. Using Kloosterman’s mixed embeddedness framework, this study examines how two sides’ diaspora relations with both the homeland and the host land serve as a strategy for developing and maintaining their businesses. This study found that the strategy used by Sariraya, involves intercultural interactions not only among the Indonesian diaspora , the homeland community, and local Japanese society, but also across cross-border Muslim networks. Beyond Klooterman's idea that only connects the diaspora with the homeland and host land, Sariraya builds a network of Muslim communities, in addition to the local community. Sariraya’s product innovations take local tastes into account, and its marketing strategy involves Muslim networks, which is the key to Sariraya’s success in maintaining  halal business in Japan.